The effect of alloy composition on instabilities in the β phase of titanium alloys. (15th April 2016) - Zheng, Yufeng; Williams, Robert E.A.; Nag, Soumya; Banerjee, Rajarshi; Fraser, Hamish L.; Banerjee, Dipankar
Abstract: A metastable nano-scale disordered precipitate with orthorhombic symmetry has been identified using high resolution scanning transmission electron microscopy. The phase, termed O′, is metastable, formed by a shuffle mechanism involving a 110 < 1 1 ̅ 0 > transverse phonon wave in samples of Ti–26Nb–2Zr (at.%) quenched from the β phase. The addition of 2% Zr to Ti–26Nb appears to suppress significantly the stability of both the 11 2 ̅ < 111 > shear and 2/3 < 111 > longitudinal phonon wave but promotes the 110 < 1 1 ̅ 0 > transverse shuffle. This results in the nano-size O′ phase being homogeneously formed in the parent β phase matrix rather than the massive α″ phase. Graphical abstract: